Glucocorticoid Regulation of Food-Choice Behavior in Humans: Evidence from Cushing's Syndrome - Moeller, Scott J.; Couto, Lizette; Cohen, Vanessa; Lalazar, Yelena; Makotkine, Iouri; Williams, Nia; Yehuda, Rachel; Goldstein, Rita Z.; Geer, Eliza B. (Frontiers in Neuroscience, 2016)
The mechanisms by which glucocorticoids regulate food intake and resulting body mass in humans are not well-understood. One potential mechanism could involve modulation of reward processing, but human stress models examining effects of glucocorticoids on behavior contain important confounds. Here, we studied individuals with Cushing’s syndrome, a rare endocrine disorder characterized by chronic excess endogenous glucocorticoids. Twenty-three patients with Cushing’s syndrome (13 with active disease; 10 with disease in remission) and 15 controls with a comparably high body mass index completed two simulated food-choice tasks (one with ‘explicit’ task contingencies and one with ‘probabilistic’ task contingencies), during which they indicated their objective preference for viewing high calorie food images versus standardized pleasant, unpleasant, and neutral images. All participants also completed measures of food craving, and approximately half of the participants provided 24-hour urine samples for assessment of cortisol and cortisone concentrations. Results showed that on the explicit task (but not the probabilistic task), participants with active Cushing’s syndrome made fewer food-related choices than participants with Cushing’s syndrome in remission, who in turn made fewer food-related choices than overweight controls. Corroborating this group effect, higher urine cortisone was negatively correlated with food-related choice in the subsample of all participants for whom these data were available. On the probabilistic task, despite a lack of group differences, higher food-related choice correlated with higher state and trait food craving in active Cushing’s patients. Taken together, relative to overweight controls, Cushing’s patients, particularly those with active disease, displayed a reduced vigor of responding for food rewards that was presumably attributable to glucocorticoid abnormalities. Beyond Cushing’s, these results may have relevance for elucidating glucocorticoid contributions to food-seeking behavior, enhancing mechanistic understanding of weight fluctuations associated with oral glucocorticoid therapy and/or chronic stress, and informing the neurobiology of neuropsychiatric conditions marked by abnormal cortisol dynamics (e.g., major depression, Alzheimer’s disease).